The –11377 C>G promoter variant of the adiponectin gene, prevalence of coronary atherosclerosis, and incidence of vascular events in men - Hoefle, Guenter; Muendlein, Axel; Saely, Christoph H.; Risch, Lorenz; Rein, Philipp; Koch, Lorena; Schmid, Fabian; Aczel, Stefan; Marte, Thomas; Langer, Peter; Drexel, Heinz (Thrombosis and Haemostasis, 2007)
No prospective data demonstrating an association between the –11377 C>G adiponectin gene promoter variant and cardiovascular risk are available. We therefore prospectively evaluated the cardiovascular risk associated with adiponectin gene single nucleotide polmorphisms (SNPs) including SNP –11377 in a consecutive series of men undergoing coronary angiography. We recorded vascular events over four years in 402 men undergoing coronary angiography for the evaluation of coronary artery disease. No significant associations of SNPs +276 G>T and +45 T>G with serum adiponectin, with significant coronary stenoses >50%, or with vascular events were observed. However, for SNP –11377 C>G, serum adiponectin levels significantly decreased (Ptrend = 0.003), and the prevalence of significant coronary stenoses significantly increased from the CC over the GC to the GG genotype (ptrend = 0.004). Prospectively, the risk of vascular events significantly increased from the CC over the CG to the GG genotype of this SNP (adjusted hazard ratios 1.555 [0.957-2.525] and 2.309 [1.067–4.998], respectively; ptrend = 0.014). The –11377 C>G adiponectin gene promoter variant is i) associated with decreased serum adiponectin levels, ii) correlated with the presence of coronary atherosclerosis and iii) significantly predictive of vascular events among men undergoing coronary angiography.
Keywords: Coronary artery disease; angiography; risk factors; cytokines; epidemiology